Research of Fault Diagnosis of Broken Rotor Bar of Asynchronous Motor Based on Wavelet Analysis - WANG Chang-ji; XU Yun-zhi (Gong-kuang zidonghua, 2012)
In view of shortcoming that common steady state fourier analysis for motor ca't analyze local spectrum characteristics of local time-domain signal, an improved wavelet packet analysis method was put forward which is applied to fault diagnosis of broken rotor bars of asynchronous motor. Through decomposition and reconstruction of the wavelet packet of motor fault signal, the method can detect fault signal frequency effectively, so as to determine fault type and possible fault part. The experiment result proved validity of the method.